Changes in Bone Mineral Density and Metabolic Parameters after Pulsatile Gonadorelin Treatment in Young Men with Hypogonadotropic Hypogonadism - Chen-Xi Li; Song-Tao Tang; Qiu Zhang (International Journal of Endocrinology)
To assess the prevalence of osteoporosis in young men with hypogonadotropic hypogonadism (HH) and to investigate the changes of BMD and metabolic parameters, a total of 22 young male patients with HH and 20 healthy controls were enrolled in the study. BMD, biochemical, and hormonal parameters were measured in two groups. Osteoporosis was more prevalent in HH patients (45.45%) than the control subjects (10.00%) (P<0.001). The patients with HH had lower BMD in lumbar spine 2–4, femoral neck, and total hip (P<0.001, for all) and higher fasting insulin (P=0.001), HOMA-IR (P=0.002), and SHBG (P<0.001) compared to the controls. After 6 months of pulsatile gonadorelin treatment, BMI (P=0.021) and BMD in lumbar spine 2–4, femoral neck, and total hip (P=0.002, P=0.003, and P=0.003, resp.) increased dramatically and total cholesterol (P=0.034), fasting insulin (P=0.025), HOMA-IR (P=0.021), and SHBG (P=0.001) decreased significantly in HH patients. The study shows a higher prevalence of osteoporosis in young men with HH. Long-term pulsatile gonadorelin treatment indicates a positive effect on BMD and metabolic parameters of HH patients.